Solve for n 2n+4=8-6(n-4)

2n+4=8-6(n-4)
Simplify 8-6(n-4).
Simplify each term.
Apply the distributive property.
2n+4=8-6n-6⋅-4
Multiply -6 by -4.
2n+4=8-6n+24
2n+4=8-6n+24
2n+4=-6n+32
2n+4=-6n+32
Move all terms containing n to the left side of the equation.
Add 6n to both sides of the equation.
2n+4+6n=32
8n+4=32
8n+4=32
Move all terms not containing n to the right side of the equation.
Subtract 4 from both sides of the equation.
8n=32-4
Subtract 4 from 32.
8n=28
8n=28
Divide each term by 8 and simplify.
Divide each term in 8n=28 by 8.
8n8=288
Cancel the common factor of 8.
Cancel the common factor.
8n8=288
Divide n by 1.
n=288
n=288
Cancel the common factor of 28 and 8.
Factor 4 out of 28.
n=4(7)8
Cancel the common factors.
Factor 4 out of 8.
n=4⋅74⋅2
Cancel the common factor.
n=4⋅74⋅2
Rewrite the expression.
n=72
n=72
n=72
n=72
The result can be shown in multiple forms.
Exact Form:
n=72
Decimal Form:
n=3.5
Mixed Number Form:
n=312
Solve for n 2n+4=8-6(n-4)

Our Professionals

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top